Impact of target volume and dose concepts on the outcomes of prostate cancer patients treated with stereotactic body radiotherapy for spinal metastases: a European multicenter cohort study - Seiler, Isabella; Meents, Johannes; Kästner, Lena; Müller, Jörg Andreas; Boda-Heggemann, Judit (Radiotherapy and oncology, 2026)
Background and purpose - The importance of metastasis-directed radiotherapy is increasing in the management of oligometastatic prostate cancer. We evaluated different target volume and dose concepts for stereotactic body radiotherapy (SBRT) of spine bone metastases (BoM) from prostate cancer in a large European cohort. - Material and methods - Data of prostate cancer patients receiving SBRT for spine BoM between 2010 and 2024 at 19 European cancer centers were retrospectively collected. Treatment volumes and dose concepts were analyzed regarding their impact on overall survival (OS), freedom from local recurrence (FFLR), biochemical recurrence-free survival (BRFS), and progression-free survival (PFS). - Results - With a median follow-up of 25.1 months (range: 1.4-77.2), 213 patients with 283 spine BoM were evaluated. 1-/3-year PFS with simultaneously integrated boost (SIB) were 85.7 %/73.9 % (BED4 [Biologically effective dose with α/β-ratio = 4 Gy] ≥ 100 Gy) and for non-SIB concepts 81.2 %/45.5 % (BED4 ≥ 100 Gy), respectively. 1-/3-year BRFS for SIB-treated BoM amounted to 81.7 %/68.4 % (BED4 ≥ 100 Gy) and for non-SIB 78.3 %/43.6 % (BED4 ≥ 100 Gy). OS was not significantly different for the evaluated dose and target volume concepts. For FFLR a significant difference was observed favoring BED4 ≥ 100 Gy. In multivariable analysis, following factors were positively associated with both PFS and BRFS: BED4 for GTVmean dose and SIB concept. Adverse events were very low, with fracture rates of 2.2 %. - Conclusion - This multicenter cohort analysis showed that SBRT of spine BoM from prostate cancer is an effective and well-tolerated treatment. Both BED and usage of a SIB concept were associated with improved PFS and BRFS. Prospective studies are needed to confirm these findings and further standardize SBRT concepts.
Online verfügbar: 8. November 2025, Artikelversion: 15. November 2025
Gesehen am 26.01.2026